2021
DOI: 10.4028/www.scientific.net/kem.884.251
|View full text |Cite
|
Sign up to set email alerts
|

Application of Natural Aromatase Blocker Towards the Level of Testosterone in Rooster Layer [<i>Gallus gallus gallus </i>(Linn., 1758)]

Abstract: Aromatase blockers are agents that can inhibit the action of the aromatase enzyme so that testosterone will not be converted to estradiol. Thus, the level of testosterone in the blood is maintained high. The purpose of this study was to evaluate the effects of natural aromatase blocker (NAB) on the level of testosterone in serum and evaluate the effectiveness of chemical testosterone. This study used 100 days old chick (DOC) of Layer chicken that divided randomly into 4 treatment groups namely P0 (control), P1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 13 publications
(15 reference statements)
1
13
0
Order By: Relevance
“…These results are in agreement with Astuti et al [17], that demonstrated that the administration of Anadara nodifera shell powder as a NAB at doses of 3.3 and 6.6 g/day, ZnSO 4 0.45 mg/kg BW, and testosterone 0.1 mL/day for 35 days did not increase the size of the comb and wattle in adult Bangkok cockerels. This was also shown by Yuneldi et al [18], where the administration of BCSP as a NAB at a dose of 0.036 mg/40 g BW and ZnSO 4 0.018 mg/40 g BW for 35 days could not increase the length and height of the day old chick (DOC) comb of male layers.…”
Section: Comb and Wattle 56 Days Post-treatmentsupporting
confidence: 71%
See 3 more Smart Citations
“…These results are in agreement with Astuti et al [17], that demonstrated that the administration of Anadara nodifera shell powder as a NAB at doses of 3.3 and 6.6 g/day, ZnSO 4 0.45 mg/kg BW, and testosterone 0.1 mL/day for 35 days did not increase the size of the comb and wattle in adult Bangkok cockerels. This was also shown by Yuneldi et al [18], where the administration of BCSP as a NAB at a dose of 0.036 mg/40 g BW and ZnSO 4 0.018 mg/40 g BW for 35 days could not increase the length and height of the day old chick (DOC) comb of male layers.…”
Section: Comb and Wattle 56 Days Post-treatmentsupporting
confidence: 71%
“…Improvement of pectoralis muscle is characterized by the increasing number of myofibers in one fascicle, myofiber area (MA), fascicle area (FA), and proliferation in the nucleus of muscle cells [9][10][11][12]. The increase in growth and the pectoralis muscle characteristics of pelung cockerels is triggered by the hormone testosterone [5,7,[13][14][15][16][17][18][19]. The hormone testosterone in male animals is produced by the testes [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aromatase blocker is a drug that can block the aromatase enzyme so that it becomes an agent that can prevent the work of aromatase enzymes so that testosterone hormone not be converted into estradiol [20] so that the concentration of testosterone in the body can be defended and spermatogenesis can increase [21,22]. [23] reported that aromatase blockers are effective in overcoming hypogonadism, as well as minimal side effects.…”
Section: The Important Role Of the Hormone Testosteronementioning
confidence: 99%